ANALISIS PESAWAT SEDERHANA DARI TUAS 1,2, & 3 - Muhammad Rizki Saputra; Lathifah Munawaroh; Amelia Putri (JURNAL ILMIAH NUSANTARA, 2025)
A simple machine is a mechanical device that can change the direction or magnitude of a force. More simply, a simple machine is a tool used to simplify work or tasks. A lever is one type of simple machine that we often encounter. This lever has three main components: a fulcrum, a load point, and a force point. The first type of lever has a fulcrum that is between the load and the applied force. The second type of lever has a load point located between the fulcrum and the force point. The third type of lever has a force point located between the fulcrum and the load. The study used a direct practical method to observe how levers 1, 2, and 3 work. This study aims to explain how levers work, compare their mechanical efficiency, and show their implementation in everyday life and in more efficient science learning. The result of this study is that we can see and differentiate between levers 1, 2, and 3, both in terms of how they are used and the types of tools that can be used. One crucial topic in science is simple machines, for example levers, which help lighten work without requiring additional energy. Levers are classified into three types based on the position of the fulcrum, load, and force, each of which has different mechanical advantages.